Learning Video Innovation Based on Pancasila Student Profiles: Exploration of the Values of Historical Places in Margarana - Yoga, Ida Bagus Made Dwitama; Agung, Anak Agung Gede; Sujana, I Wayan (Indonesian Values and Character Education Journal, 2024)
Learning media is a tool or infrastructure used in learning activities and is useful in helping the teaching and learning process and increasing students' motivation to learn. This research aims to develop video media for teaching values based on Pancasila student profiles at the Margarana historical site for elementary school students. The test subjects for this research were material/content experts, design experts, learning media experts, and 28 students. This research uses the ADDIE development model, questionnaire and test data collection methods, quantitative descriptive data analysis techniques, and t-test inferential statistical analysis. The research results found that the design was a learning video and obtained a score of 90.90% with very good qualifications. The results of the expert test and user test showed that the media content expert test results obtained a score of 93.18%, the results of the learning design expert test obtained a score of 90%, the learning media expert test results obtained a score of 91.66%, the individual test results obtained a score of 90.96%, and the small group test results obtained a score of 90.00%, so this learning video received very good qualifications. It is worthy of use. The product effectiveness results were obtained from the t-test statistical test, namely t-count = 6.953. For db = 27 and a significance level of 5%, the t-table figure = 1.703. So, t-count > t-table, H0 is rejected, and H1 is accepted, meaning there is a significant difference in science learning outcomes before and after video learning media. Thus, the learning video media in this research is effectively used in the science content of my area material.